2016
DOI: 10.1115/1.4032904
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Water Jet Trajectory by a Nonuniform Electric Field in Water Jet Material Processing

Abstract: In spite of its applications in macromanufacturing processes, water jet processing has not been extensively applied to the field of micromanufacturing owing to its poor tolerance and lack of effective control of the jet impingement position. This paper investigates the phenomenon of liquid dielectrophoresis (LDEP) using a localized nonuniform static electric field to deflect and control the jet's trajectory at the microscale for a water jet in air. A new analytical modeling approach has been attempted by repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Figure 6b illustrates the details of a DEP-based particle separation method in a microfluidic device [288]. DEP is a phenomenon where a chargeneutral but polarizable particle experiences a force in a non-uniform electric field due to the interaction of the particle's dipole and the spatial gradient of the electric field [302][303][304][305]. Jason et al have demonstrated a methodology of particle separation based on DEP in a microfluidic device whose top and cross-sectional views are shown in Figure 6b(i,ii), respectively [288].…”
Section: Sorting Single Particlesmentioning
confidence: 99%
“…Figure 6b illustrates the details of a DEP-based particle separation method in a microfluidic device [288]. DEP is a phenomenon where a chargeneutral but polarizable particle experiences a force in a non-uniform electric field due to the interaction of the particle's dipole and the spatial gradient of the electric field [302][303][304][305]. Jason et al have demonstrated a methodology of particle separation based on DEP in a microfluidic device whose top and cross-sectional views are shown in Figure 6b(i,ii), respectively [288].…”
Section: Sorting Single Particlesmentioning
confidence: 99%
“…The motion, deformation, and instability of charged liquid jets were examined by using a nozzle-ring electrode apparatus by Hokmabad et al [20]. A preliminary study on manipulating the trajectory of a low-pressure water jet with corresponding modeling in COMSOL was performed by Mohanty et al [21]. Furthermore, Jones discussed the possibility, capability, and applications of DEP liquid actuation at the microscale [22].…”
Section: Introductionmentioning
confidence: 99%